Impact of diabetes mellitus on the outcomes of subjects with hypertrophic cardiomyopathy: A nationwide cohort study. (April 2022) - Lee, Hyun-Jung; Kim, Hyung-Kwan; Kim, Bong-Seong; Han, Kyung-Do; Rhee, Tae-Min; Park, Jun-Bean; Lee, Heesun; Lee, Seung-Pyo; Kim, Yong-Jin
Highlights: The clinical impact of ageing-related diseases such as diabetes is becoming increasingly important in HCM. A nationwide cohort of 9, 883 subjects with HCM. Diabetes is associated with 3.5-fold higher risk of end-stage renal failure in HCM. Diabetes is associated with 15% higher risk of heart failure in HCM. Insulin-treated diabetes patients are at highest risk. Abstract: Aims: Diabetes mellitus (DM) often coexists in elderly hypertrophic cardiomyopathy (HCM) patients; however, its impact on clinical outcomes is unclear. Methods: We compared clinical outcomes according to the presence of DM in a nationwide HCM cohort. Results: In 9, 883 HCM subjects (mean age 58.5 ± 13.1, men 71.7%), 1, 327 (13.4%) had DM. During follow-up (mean 5.9 ± 2.5 years), end-stage renal disease (ESRD) progression, coronary events (myocardial infarction, coronary revascularization), heart failure (HF), cardiovascular mortality, and all-cause mortality occurred in 80 (0.8%), 365 (3.7%), 1, 558 (15.8%), 354 (3.6%), and 877 (8.9%) subjects, respectively. DM HCM subjects had significantly higher risks of ESRD progression (HR 3.49, 95% CI 2.20–5.54) and HF (HR 1.15, 95% CI 1.01–1.32) compared to non-DM HCM subjects, independent of age, sex, ischemic heart disease, atrial fibrillation, and other comorbidities. There was a tendency for greater risk of ESRD progression, HF, and all-cause death in subjects with more advanced stage of DM ( p -for-trend < 0.05 for all). Insulin-treated DM was associated with the highest risk. Conclusions: DM HCM subjects have higher risk of ESRD progression and HF. Considering the extended life expectancy of HCM and increasing number of elderly HCM subjects, active surveillance and management of DM-related outcomes should be highlighted.